2016
DOI: 10.1177/1087054716664412
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Nerve Fiber Layer Thickness in Children With ADHD

Abstract: This is the first study examining the RNFL thickness in ADHD. Our findings showed that nasal RNFL thickness was lower, indicating reduced unmyelinated axons in the retina of children with ADHD. The results of this study support the evidence that ADHD involves a lag in cortical maturation and this is measurable in the retina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 40 publications
4
29
3
Order By: Relevance
“…Herguner et al have compared the RNFL thickness measurement results of 45 ADHD diagnosed children with a healthy group of 45 children; and they have found the RNFL thickness in the nasal quadrant of the ADHD diagnosed children to be significantly lower than the control group. Moreover, they have reported a negative correlation between the severeness of the symptoms and the RNFL thickness (27). In our study, although a thinning in the left and right eye average RNFL thickness detected in the patient group, it was not statistically significant.…”
Section: Discussioncontrasting
confidence: 77%
“…Herguner et al have compared the RNFL thickness measurement results of 45 ADHD diagnosed children with a healthy group of 45 children; and they have found the RNFL thickness in the nasal quadrant of the ADHD diagnosed children to be significantly lower than the control group. Moreover, they have reported a negative correlation between the severeness of the symptoms and the RNFL thickness (27). In our study, although a thinning in the left and right eye average RNFL thickness detected in the patient group, it was not statistically significant.…”
Section: Discussioncontrasting
confidence: 77%
“…Hergüner et al found that the ADHD group's macular thickness did not differ from age-matched controls, but the RNFL is reduced in the ADHD group. They also suggested that there was a negative correlation between RNFL thickness and ADHD symptom severity [20]. In parallel with the previous result, we found RNFL thickness was lower in the ADHD group than in the control group, but this difference was not statistically significant.…”
Section: Discussionsupporting
confidence: 89%
“…To the best of our knowledge, there are only two studies evaluated the RNFL and macular thickness of eyes of children and adolescents with ADHD which is a neurodevelopmental disorder. Hergüner et al found that the ADHD group's macular thickness did not differ from age-matched controls, but the RNFL thickness is reduced in the ADHD group [20]. In another study, children and adolescents with ADHD and Oppositional Defiant Disorder (ODD) accompanying ADHD compared to healthy controls, no significant difference was found in terms of RNFL but the ganglion cell layer of the retina was found to be thinner in ADHD and ADHD + ODD groups [21].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, Iseri et al have demonstrated a relationship between retinal pathology and cognitive impairment in an AD group [14]. As for ADHD, Hergüner reported lower RNFL thickness, but no difference in macular thickness [15].…”
Section: Introductionmentioning
confidence: 99%